Effect of a Combination of Auxin and Gibberellin Hormones on the Growth and Production of Cayyey Chilli Plant (Capsicum frutescens L.) - Sokmawati, Dwi (Contributions of Central Research Institute for Agriculture, 2023)
This research aims to determine the effect of giving a combination of the hormones auxin and gibberellin on the growth and production of cayenne pepper plants. The design used in this research was a Completely Randomized Design (CRD) with 25 treatments and 2 replications using combined auxin and gibberellin concentrations of 0,50,100,150,200 ppm. It is applied three times, namely when soaking the seeds and spraying when flower buds form and after the young plants bear fruit. The research results were analyzed using Kruskall-Wallis which showed that there was no effect of giving a combination of auxin and gibberellin hormones on all observation parameters. Growth parameters including plant height and number of leaves were highest in treatment 17, namely a combination of 150 ppm auxin and 50 ppm gibberellin with a value of 21.46 cm and 18.9 fruit. Production yield parameters which include anthesis time and the highest number of flowers in treatment 17, namely a combination of 150 ppm auxin and 50 ppm gibberellin with values of 35.5 days and 3.94 fruit, then the number of fallen flowers and the lowest number of fallen fruit in treatment 21, namely the combination 200 ppm auxin and 0 ppm gibberellin with a value of 1.28 fruit and 0 fruit, then the highest number of fruit was in treatment 7, namely a combination of 50 ppm auxin and 50 ppm gibberellin with a value of 43.5 fruit. The most optimal combination in the P17 treatment is a combination of 150 ppm auxin and 50 ppm gibberellin.